Liliputella, a new genus of microscopic, wingless and blind Scydmaenini of the Bismarck Islands (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
Liliputella microscopica gen. & sp. nov. is described and placed in the tribe Scydmaenini. This taxon is known from a single male collected on Dyaul Island, the Bismarck Archipelago (Papua New Guinea). With only 0.68 mm of body length, this beetle is one of the smallest within Scydmaenini. Liliputella microscopica is also blind, wingless, strongly flattened and lightly pigmented, suggesting a possible subterraneous habitat. Alternatively, a large and deep ventral cephalic cavity, a unique character not known in any other species of Scydmaeninae, may be a glandular structure indicative of myrmecophily or termitophily. Liliputella shares several interesting characters with genera that also include blind, wingless and presumably subterraneous species, Eudesis and Pseudoeudesis, e.g., humeral denticles, adjacent antennal insertions or strikingly short tarsi. Morphological structures of the new genus are compared with those of other Scydmaenini, and a preliminary identification key to the genera of this tribe is presented. Possible morphological adaptations of Liliputella to miniaturization are also discussed.